Three international research grant from Southeast Asian Ministers Of Education Organization - Sorooshian, Shahryar; M., Waris; Senthil Kumar, T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (Faculty of Industrial Management, 2016)
Congratulations to Dr. Diyana Kamarudin for achieving Three International research grant from Southeast Asian Ministers Of Education Organization